Photodynamic diagnosis using 5‐aminolevulinic acid during gastrectomy for gastric cancer. Issue 3 (8th November 2013) - Namikawa, Tsutomu; Inoue, Keiji; Uemura, Sunao; Shiga, Mai; Maeda, Hiromichi; Kitagawa, Hiroyuki; Fukuhara, Hideo; Kobayashi, Michiya; Shuin, Taro; Hanazaki, Kazuhiro
Abstract Background and Objectives Five‐aminolevulinic acid (ALA) has received much attention recently as a new‐generation photosensitive substance for photodynamic diagnosis (PDD). This study aimed to investigate the feasibility of intraoperative PDD using ALA to identify gastric cancer. Methods Intraoperative PDD was carried out in 26 lesions of 21 patients with gastric cancer. Before surgery, 1.0 g of ALA solution was given orally through a stomach tube. After tumor resection, resected specimens were investigated by an endoscopic PDD system, and red fluorescence‐positive lesions were compared with the pathological result. Results Red fluorescence was detected in 15 lesions of 11 patients. The sensitivity, specificity, and accuracy of PDD using ALA in detecting gastric cancer were 57.7, 100, and 66.7%, respectively. The incidence of laparoscopic surgery was significantly lower in the PDD‐positive group than in PDD‐negative cases (18.2% vs. 60.0%; P = 0.049), while that of intestinal type tumor was significantly higher in PDD‐positive compared to PDD‐negative patients (93.3% vs. 27.3%; P < 0.001). Conclusions Fluorescence navigation by PDD provides good visualization and detection of gastric cancer lesions, and might be particularly useful for intestinal type gastric cancer. Thus, PDD using ALA seems to be a promising diagnostic tool for gastric cancer. J. Surg. Oncol. 2014 109:213–217. © 2013 Wiley Periodicals, Inc.